2002
DOI: 10.1142/s0192415x02000661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Red Ginseng Upon Postoperative Immunity and Survival in Patients with Stage III Gastric Cancer

Abstract: In this paper, we present evidence that the red ginseng powder from Panax ginseng C.A. Meyer inhibits the recurrence of AJCC stage III gastric cancer and shows immunomodulatory activities during postoperative chemotherapy, after a curative resection with D2 lymph node dissection. Flow cytometric analyses for peripheral T-lymphocyte subsets showed that the red ginseng powder restored CD4 levels to the initial preoperative values during postoperative chemotherapy. Depression of CD3 during postoperative chemother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…For example, ginseng could inhibit the recurrence of American Joint Committee on Cancer (AJCC) stage III gastric tumor and showed immunomodulatory activities during post-operative chemotherapy. Moreover, red ginseng also increased the overall survival of patients during post-operative chemotherapy in comparison with the matched control (127). Additionally, Li (128) has reported that the ginseng-containing Shen-Qi injection could reduce the toxic effects produced by chemical agents in patients suffering from digestive tract tumors.…”
Section: Clinical Aspects Of Ginsengmentioning
confidence: 98%
“…For example, ginseng could inhibit the recurrence of American Joint Committee on Cancer (AJCC) stage III gastric tumor and showed immunomodulatory activities during post-operative chemotherapy. Moreover, red ginseng also increased the overall survival of patients during post-operative chemotherapy in comparison with the matched control (127). Additionally, Li (128) has reported that the ginseng-containing Shen-Qi injection could reduce the toxic effects produced by chemical agents in patients suffering from digestive tract tumors.…”
Section: Clinical Aspects Of Ginsengmentioning
confidence: 98%
“…[31][32][33][34] Case control 35,36) and cohort studies 37) have reported that ingesting ginseng could significantly decrease the mortality from cancer to some extent and a clinical trial study indicated that Korean red ginseng powder might improve postoperative survival as well as restore immunity in patients with advanced gastric cancer. 38) The anti-cancer activity can be mainly ascribed to ginsenosides. 34) Deglycosylated forms of PPD type ginsenosides such as cK have potent cytotoxicity and inhibit tumor cell invasion.…”
Section: )mentioning
confidence: 99%
“…11,12 In human studies, the regular use of ginseng has been shown to improve both the survival and the quality of life among breast cancer patients, 13 and red ginseng powder was reported to inhibit the recurrence of stage III gastric cancer. 14 Water-soluble ginseng extracts consisting primarily of ginsenosides and acidic polysaccharides have been the subject of extensive chemotherapeutic investigation. In contrast, our research has focused on the anticancer activity of lipid-soluble ginseng extracts because it was reported that they inhibit the proliferation of human colon, rectal, liver, and breast cancer cells in vitro [15][16][17] and extend the survival time of mice bearing murine ascetic sarcoma-180 by about 1.5 to two times in vivo.…”
Section: Introductionmentioning
confidence: 99%